Satisfaction among counselling interns: the implicit role of supervisory style - Uba, Ikechukwu; Hassan, Siti Aishah; Mohd Ali, Nur Hafizah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Satisfaction among counseling interns is a relatively understudied problem among scholars. This survey therefore examined the function of supervisory style in the maintenance and sustenance of the phenomenon among counselling interns. The participants of the study included 138 counselling students aged 22 to 27(M age = 23, SD =1.15) from four selected Universities in Malaysia. Supervisory style was measured with the adapted supervisory style inventory (Hart & Nance, 2003), while satisfaction among counselling interns was measured with the supervisory satisfaction questionnaire (SSQ; Ladany, Hill & Nutt, 1996). Adaptive supervision in counselor training (Howard, Nance & Myers, 1986) and working alliance model of supervision (Bordin, 1983) were used as framework for the investigation. Findings of the inquiry revealed a significant and positive relationship between three components of supervisory style and counselling satisfaction (directive, supportive and counsellor style). The results highlighted the unique contribution of supportive teacher style (R2 = .24, F (3, 134) =13.93, p < .001) in the satisfaction of the counseling interns. Future researchers may utilize a large sample comprising counseling intern’s, their supervisors and some relevant demographic variables.